Outdoor Concert Noise: The Kitchener, Ontario Experience - Arnold, Lucas; Chin-Quee, Darron; Penton, Scott R.L. (Canadian Acoustics, 2017)
Outdoor music festivals have the potential to cause adverse public reaction and noise complaints, particularly from surrounding residential neighbourhoods. At times, seemingly random noise complaints occur, with clusters of complaints occurring in areas well removed from the venue, while adjacent nearby neighbourhoods experience little to no noise. This paper examines the experience in Kitchener, Ontario with The Ever After Music festival, a three-day electronic music festival run in the City since 2015. In its inaugural year, the festival prompted 57 noise complaints, with 7 the next year in 2016, and approximately 100 alone on the final concert night of 2017. Efforts of the promoters and the City to reduce noise impacts, including controls that were put in place, are reviewed and compared to those used in other jurisdictions. Potential event specific relationships between complaint locales, weather, and meteorological effects are also reviewed, as determined through noise propagation modelling and where available, measured sound levels.